Thermal decomposition of derivatives of organocobalt(III) [RCoIII(bae)] and [RCoIII(bae)]H2O] - Mercadante, Amauri; Ionashiro, Massao; Benedetti, Assis Vicente; Dockal, Eduard Ralf (Eclética Química, 1989)
.